2021
DOI: 10.1186/s12974-021-02123-0
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the lesion site: minocycline augments inflammation and anxiety-like behavior following SCI in rats through action on the gut microbiota

Abstract: Background Minocycline is a clinically available synthetic tetracycline derivative with anti-inflammatory and antibiotic properties. The majority of studies show that minocycline can reduce tissue damage and improve functional recovery following central nervous system injuries, mainly attributed to the drug’s direct anti-inflammatory, anti-oxidative, and neuroprotective properties. Surprisingly the consequences of minocycline’s antibiotic (i.e., antibacterial) effects on the gut microbiota and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 94 publications
0
17
0
1
Order By: Relevance
“…FMT could increase the amount of fecal SCFAs and downregulate IL-1b/NF-kB signaling in the spinal cord and NF-kB signaling in the gut following SCI (118). A recent study also reported that minocycline treatment attenuated SCI-induced anxiety-like behavior and systemic inflammatory response via altering the Firmicutes/Bacteroidetes ratio (119). Engineered liposomes targeting the MGBA may also be a potential treatment (126).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…FMT could increase the amount of fecal SCFAs and downregulate IL-1b/NF-kB signaling in the spinal cord and NF-kB signaling in the gut following SCI (118). A recent study also reported that minocycline treatment attenuated SCI-induced anxiety-like behavior and systemic inflammatory response via altering the Firmicutes/Bacteroidetes ratio (119). Engineered liposomes targeting the MGBA may also be a potential treatment (126).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Pooled data for two RCTs recently showed that minocycline, a specific microglial inhibitor, improved depressive symptoms and reduced the severity of anxiety in a total of 112 participants with major depressive disorders ( Zazula et al, 2021 ). However, there is concern about other risks of using minocycline to treat anxiety and depression because it is also an antibiotic ( Schmidt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vc microglia in female rats might not be an inflammatory phenotype after re-incision. Minocycline is widely used in glial research to inhibit the transformation of microglia toward an inflammatory phenotype 8 , 16 and does not affect microglial ramification or IBA1 expression under normal conditions 25 , 26 . Therefore, it is possible that minocycline unaffected Vc microglia in female rats even after re-incision.…”
Section: Discussionmentioning
confidence: 99%
“…All rats were acclimated to the testing environment for 5 days. The von Frey filaments (4,6,8,10,15,26,30,40,50,60, and 80 g) were applied to the left whisker pad skin according to the method described previously 47 . Each filament was used ascending manner.…”
Section: Measurement Of Head Withdrawal Thresholdmentioning
confidence: 99%